2018
DOI: 10.1097/corr.0000000000000446
|View full text |Cite
|
Sign up to set email alerts
|

Early Maturity as the New Normal: A Century-long Study of Bone Age

Abstract: Level II, prognostic study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 34 publications
1
17
1
1
Order By: Relevance
“…Second, 64.7% (515/796) of children with normal-weight had a SA lower than CA (Fig. 4 b) in this study, which disagrees with a previous study that encouraged a general advancement with an improvement in the nutritional level of modern people [ 29 ]. Third, no statistical difference was observed in relative SA between males and females among children aged 3–6 years (Table 3 ); this result was inconsistent with a previous conclusion that the development of SA occurs earlier in females than in males from birth to early adolescence [ 30 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Second, 64.7% (515/796) of children with normal-weight had a SA lower than CA (Fig. 4 b) in this study, which disagrees with a previous study that encouraged a general advancement with an improvement in the nutritional level of modern people [ 29 ]. Third, no statistical difference was observed in relative SA between males and females among children aged 3–6 years (Table 3 ); this result was inconsistent with a previous conclusion that the development of SA occurs earlier in females than in males from birth to early adolescence [ 30 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Another consideration was that nutritional status was an important factor influencing both accelerated skeletal maturation and overweight/obesity. Several studies indicated that the secular trend of earlier maturation could be caused by improved nutrition and socioeconomic environments [ 29 , 38 – 40 ], which is the same reason for the increasing prevalence of childhood overweight and obesity worldwide [ 2 , 41 ]. Conversely, as shown in the results, 69.6 and 64.7% of children with thin and normal-weight had lower SA than CA, respectively (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…These results supported the findings of previous research on children and adolescents [10,11,13]. Second, 64.7% (515/796) of children with normal-weight had a SA lower than CA (Figure 2b) in this study, which disagrees with a previous study that encouraged a general advancement with an improvement in the nutritional level of modern people [17]. Third, no statistical difference was observed in relative SA between males and females among children aged 3-6 years (Table 10 2); this result was inconsistent with a previous conclusion that the development of SA occurs earlier in females than males from birth to early adolescence [18].…”
Section: Discussionsupporting
confidence: 78%
“…The occurrence of a secular trend was noted in skeletal maturation in South African children (both white and black) [30]. Boeyer indicated that the initiation and completion of epiphyseal fusion occur at substantially younger ages in normally developing children born in 1995 than those born in 1935 (both male and female) [17]. These studies indicated that the secular trend of earlier maturation is attributed to the removal of growth constraints through improved nutrition, healthcare, and socioeconomic environments [26,31].…”
Section: Discussionmentioning
confidence: 97%
“…However, children with considerably advanced BA (BA-CA ≥ 2 years) have been observed in different populations: approximately 10% of healthy prepubescent Chinese children (unpublished observations by our research team); up to 21% of healthy children in the United States 3 ; and 48.7% of girls with isolated premature thelarche, who should not have significantly advanced BA 4 , 5 . Moreover, a long-term trend of overall accelerated bone maturation in children has been observed in many countries 3 , 6 10 . Unfortunately, existing research results cannot fully explain the acceleration of bone maturation in children.…”
Section: Introductionmentioning
confidence: 99%